2022
DOI: 10.1002/ctm2.805
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of plasma biomarkers for colorectal cancer diagnosis via untargeted and targeted quantitative metabolomics

Abstract: Dear Editor, Colorectal cancer (CRC) is a major cause of cancer-related mortality worldwide. 1 Shifting the detection of CRC to earlier stages via massive screening has considerably reduced mortality. 2 Metabolomics has shown great potential in the identification of noninvasive biomarkers of CRC. However, the huge number and inconsistent reports of putative markers make choosing the most appropriate biomarkers difficult. The aim of this study was to identify the metabolic markers of CRC by a multi-step strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Te levels of LPCs in mice tended to return to normal after the administration of SJE. Maoqing Wang et al [42] identifed fve biomarkers of CRC, including LysoPC (14 : 0), LysoPC (16 : 0), LysoPC (18 : 0), LA, and tryptophan, through metabolomics studies. In this study, we found that LysoPC (16 : 0), LysoPC (18 : 0), LA, and tryptophan were all signifcantly regulated by SJE, providing supporting evidence for the efectiveness of SJE.…”
Section: Discussionmentioning
confidence: 99%
“…Te levels of LPCs in mice tended to return to normal after the administration of SJE. Maoqing Wang et al [42] identifed fve biomarkers of CRC, including LysoPC (14 : 0), LysoPC (16 : 0), LysoPC (18 : 0), LA, and tryptophan, through metabolomics studies. In this study, we found that LysoPC (16 : 0), LysoPC (18 : 0), LA, and tryptophan were all signifcantly regulated by SJE, providing supporting evidence for the efectiveness of SJE.…”
Section: Discussionmentioning
confidence: 99%
“…Feature variables were screened from DEPs using the least absolute shrinkage and selection operator (LASSO) and a random forest algorithm, respectively, and the diagnostic significance of proteins with large AUCs was examined. 13 A comprehensive comparison of the results of the three aforementioned analyses enabled the most reliable variables to be determined. These were used as the feature variables for the model establishment.…”
Section: Establishment and Evaluation Of The Is Modelmentioning
confidence: 99%
“…In contrast, a study based on sputum metabolomics observed the opposite trend in patients with lung cancer ( 46 ), and the difference in the distribution of tryptophan in blood and sputum may be the result of increased tryptophan consumption by tumor cells. In addition to lung cancer, there are significant changes in circulating blood tryptophan levels in colorectal, pancreatic, and bladder cancer ( 32 , 44 , 45 ).…”
Section: Metabolomic Biomarkers For Cancer Screening and Diagnosismentioning
confidence: 99%
“…Arachidonic acid derivatives such as prostaglandins and leukotrienes are important mediators involved in the inflammatory response and tumor development ( 113 ). Studies have identified significantly lower blood linoleic acid levels in patients with esophageal cancer ( 31 ), gastric cancer ( 63 ), and colon cancer ( 44 ), suggesting a key role of linoleic acid metabolism in gastrointestinal tumors.…”
Section: Metabolomic Biomarkers For Cancer Screening and Diagnosismentioning
confidence: 99%